Where and when will we observe cloud changes due to climate warming?. Issue 23 (2nd December 2014) - Chepfer, H.; Noel, V.; Winker, D.; Chiriaco, M.
Abstract: Climate models predict that the geographic distribution of clouds will change in response to anthropogenic warming, though uncertainties in the existing satellite record are larger than the magnitude of the predicted effects. Here we argue that cloud vertical distribution, observable by active spaceborne sensors, is a more robust signature of climate change. Comparison of Atmospheric Model Intercomparison Project present day and +4 K runs from Coupled Model Intercomparison Project Phase 5 shows that cloud radiative effect and total cloud cover do not represent robust signatures of climate change, as predicted changes fall within the range of variability in the current observational record. However, the predicted forced changes in cloud vertical distribution (directly measurable by spaceborne active sensors) are much larger than the currently observed variability and are expected to first appear at a statistically significant level in the upper troposphere, at all latitudes. Key Points: Cloud vertical distribution is sensitive to climate warming Spaceborne lidar can measure forced cloud change Forced trends in cloud profiles occur at altitudes above 5 km